Functional second harmonic generation microscopy probes molecular dynamics with high temporal resolution - Förderer, Moritz; Georgiev, Tihomir; Mosqueira, Matias; Fink, Rainer; Vogel, Martin (Biomedical optics express, 2016)
Second harmonic generation (SHG) microscopy is a powerful tool for label free ex vivo or in vivo imaging, widely used to investigate structure and organization of endogenous SHG emitting proteins such as myosin or collagen. Polarization resolved SHG microscopy renders supplementary information and is used to probe different molecular states. This development towards functional SHG microscopy is calling for new methods for high speed functional imaging of dynamic processes. In this work we present two approaches with linear polarized light and demonstrate high speed line scan measurements of the molecular dynamics of the motor protein myosin with a time resolution of 1 ms in mammalian muscle cells. Such a high speed functional SHG microscopy has high potential to deliver new insights into structural and temporal molecular dynamics under ex vivo or in vivo conditions.
Gesehen am 20.05.2020